2011
DOI: 10.1016/j.cbi.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol-A suppresses neurite extension due to inhibition of phosphorylation of mitogen-activated protein kinase in PC12 cells

Abstract: An endocrine disrupter, bisphenol-A is widely used in t he product ion of plast ics and coating s. Recent ly, it was reported that bisphenol-A affected neurotransmitters in the mammalian brain. On t he basis of these reports, it was considered that bisphenol-A affected neuronal different iat ion. In t his study, the morphological changes in nerve growth factor (NFG)-induced different iat ion caused by bisphenol-A were confir med using a PC12 cell system. When a low concentrat ion of bisphenol-A was added to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 44 publications
2
24
2
Order By: Relevance
“…In line with this, the expression of NF-200 was also reduced. These results may not be surprising because BPA has been long known to be capable of disrupting normal neuronal development and suppressing the outgrowth of neurites [21,54]. Thus, with the reduced number of axons to be myelinated, less amount of OLs/MBP may be sufficient to support axonal myelination in hippocampus resulting in relatively intact myelination of individual axons.…”
Section: Discussionmentioning
confidence: 50%
“…In line with this, the expression of NF-200 was also reduced. These results may not be surprising because BPA has been long known to be capable of disrupting normal neuronal development and suppressing the outgrowth of neurites [21,54]. Thus, with the reduced number of axons to be myelinated, less amount of OLs/MBP may be sufficient to support axonal myelination in hippocampus resulting in relatively intact myelination of individual axons.…”
Section: Discussionmentioning
confidence: 50%
“…We previously showed that BPA decreased the Bdnf gene expression in embryonic hypothalamic cells and affected the BDNF-NTRK2 neurotrophin system (10). Seki et al (11) have found that BPA causes morphological changes in NGFinduced differentiation and inhibits neurite extension in a PC12 cell line. It has also been reported to induce changes in both dendritic and synaptic development in foetal hypothalamic cells (12).…”
mentioning
confidence: 99%
“…In neuronal or neuronal-like cells, neuronal differentiation is decreased in pheochromocytoma PC12 cells in pre-exposure to BPA (0.1, 1, 10 or 100 nM) for one week, longer or a week followed by a week's withdrawal [33]. PC12 cells treated with 43.8 nM BPA for 5 days suppress neurite extension through inhibition of phosphorylation of mitogen-activated protein kinase [19]. Rats exposed to 10 or 100 nM BPA for 7 days increases both MAP2 (microtubule associated protein-2) and synapsin I-positive areas for neuronal development as well as synaptic densities in hypothalamic neurons and glias [18].…”
Section: Discussionmentioning
confidence: 99%
“…BPA also causes adverse effects on neuronal morphology and functions as to interrupting neuronal dendritic and synaptic development in cultures of fetal rat hypothalamus cells at 10 and 100 nM [18]. BPA suppresses neurite extension by inhibiting phosphorylation of mitogen activated protein kinase (MAPK) in rat pheochromocytoma PC12 cells differentiated neuronal-like cells [19]. Furthermore, perinatal exposure to BPA causes GABAergic disinhibition and dopaminergic enhancement that is related to abnormal cortical basolateral amygdala synaptic transmission and plasticity; this effect may be responsible for hyperactivity and attention deficit in BPA-rats [20].…”
Section: Introductionmentioning
confidence: 99%